ナンキョク ショウワ キチ ニオケル タンパ デンパン ジッケン ケッカ ニホン ナンキョク チイキ カンソクタイ ノ ホウコク - 貝沼, 昭司; カイヌマ, ショウジ; 城, 功; ジョウ, イサオ; 山岡, 誠; ヤマオカ, マコト; 一之瀬, 優; イチノセ, マサル; 坂元, 敏朗; サカモト, トシロウ; KAINUMA, Syoji; SHIRO, Isao; et al. (国立極地研究所, 1972)
P(論文) Continuous measurement of the field strength of NHK's overseas broadcasting waves (JOB, 11.815MHz) was carried out from April, 1970, to February, 1971. The diurnal variations in field strength were not found at the equinox, but in other months the field strength dropped after sunset. The night-time signals at Syowa Station were received mainly through the long path on the great circle. The mode of propagation varies with the condition of the ionosphere, and the mixed mode (e. g. E plus F layer reflection waves) is often predominant. At the main phase of sudden commencement of magnetic storm, the field strength abruptly drops, and this effect must be taken into consideration for the operation of communications. For the purpose of experimental studies of the radio communication in high latitudes, it is planned to continue the field strength measurement on the routine basis in the future. departmental bulletin paper